Risk factors for intensive care admission in childhood patients with COVID-19: results of the German nationwide inpatient sample - Keller, Karsten; Sagoschen, Ingo; Schmitt, Volker H.; Sivanathan, Visvakanth; Farmakis, Ioannis T.; Hahad, Omar; Koelmel, Sebastian; Schmidt, Frank P.; Espinola-Klein, Christine; Konstantinides, Stavros; Münzel, Thomas; Lurz, Philipp; et al. (Respiratory medicine, 2025)
Background - COVID-19 pandemic research efforts have mainly focused on adults, but data in paediatric populations are sparse. - Methods - We used the German nationwide-inpatient-sample analysing all hospitalized children ≤18 years with confirmed COVID-19-diagnosis in Germany during the year 2020, stratified for intensive care unit (ICU) admission. - Results - Overall, 3360 hospitalization-cases of children ≤18 years with COVID-19-infection were diagnosed in Germany 2020 (median age 7.0 [IQR 0.0-15.0] years, 49.8 % female); among them 4.3 % were admitted on an ICU. In-hospital death occurred in five patients with and three without ICU admission (3.5 % vs. 0.1 %, P < 0.001) and ICU admission was independently associated with increased case-fatality (OR 21.573 [95%CI 4.191-111.044], P < 0.001). Obesity (OR 3.419 [95%CI 1.300-8.993], P = 0.013), diabetes mellitus (OR 6.929 [95%CI 3.327-14.432], P < 0.001), pneumonia (OR 7.373 [95%CI 4.823-11.271], P < 0.001), acute respiratory distress syndrome (ARDS) (OR 48.058 [95%CI 11.689-197.588], P < 0.001) and multisystem inflammatory syndrome caused by COVID-19 (OR 9.573 [95%CI 3.036-30.191], P < 0.001), heart failure (OR 64.509 [95%CI 24.462-170.121], P < 0.001), myocarditis (OR 4.682 [95%CI 1.278-17.149], P = 0.020), acute and/or chronic kidney failure (OR 7.946 [95%CI 3.606-17.508], P < 0.001), cancer (OR 5.220 [95%CI 2.599-10.485], P < 0.001) and liver diseases (OR 5.501 [95%CI 2.177-13.899], P < 0.001) were associated with an ICU admission. - Conclusion - Proportion of hospitalized paediatric COVID-19-patients admitted on ICU in Germany was low with 4.3 % accompanied by 3.5 % case-fatality rate. Independent factors for ICU admission comprised cardio-vascular risk factors, comorbidities, and complications of COVID-19.